Identification of novel antioxidant peptide from porcine plasma hydrolysate and its effect in in vitro digestion/HepG2 cells model. Issue 4 (8th July 2021) - Li, Gaoshang; Zhan, Junqi; Hu, Lingping; Yuan, Chunhong; Ying, Xiaoguo; Hu, Yaqin
Abstract: A novel antioxidant peptide EDEQKFWGK from porcine plasma hydrolysate (PPH) was separated by chromatography, HPLC, and identified by LC‐MS/MS. Results showed that EDEQKFWGK had better antioxidant ability (Hydroxyl RAS 32.19%, ABTS RAS 92.93% and DPPH RAS 26.76%) compared with glutathione (30.11%, 82.01%, 26.44%) due to the presence of hydrophobic, aromatic acids (F, W) and acidic amino acids (E, D), decreasing ROS by providing hydrogen atom and chelating metal ions. Furthermore, the antioxidant properties of synthetic EDEQKFWGK still significant despite in vitro digestion because of the production of smaller active peptide. Additionally, it could increase SOD, CAT, GSH‐Px to resist oxidative damage in HepG2 cells by inhibiting ROS (O2 −, OH·), forming complexes to prevent OH· from destroying DNA and binding to ARE to promote antioxidase expression. Thereby, the novel peptide EDEQKFWGK from porcine plasma had much stable antioxidant properties and hade great potential in formulating functional foods. Practical applications: This research isolated a novel antioxidant peptide. Moreover, the antioxidant effects of peptide were confirmed under the in vitro digestion model and oxidative damage HepG2 cells model. The results showed the antioxidant peptide could play better effect after digestion and protect the cells from oxidative damage. These data could expand the sequence data of antioxidant peptides and promote the high‐value utilization of PPH. Abstract : A novel antioxidant peptide was isolated and identified by chromatography, HPLC and LC‐MS/MS. The peptide had stable antioxidation under in vitro digestion model. The peptide had cytoprotective effect on oxidative damage HepG2 cells induced by H2 O2 .